2011
DOI: 10.1111/j.1365-2621.2011.02702.x
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide and methylglyoxal formation in potato chips by microwaving and frying heating

Abstract: In our present paper, the effect of important a-dicarbonyl compounds of methylglyoxal on the formation of acrylamide was quantified in potato chips systems. Methylglyoxal was regarded as the main a-dicarbonyl compound, and its formation was detected by HPLC method. There heating methods were used to study the effect on acrylamide formation. The results showed that microwaving treatment could form more acrylamide compared with frying method. After 2 min of microwaving treatment at 700 W, the acrylamide content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…As to the processes, higher TFA were quantified in the DF, but always below 0.05%, corresponding to low amounts from a health point of view. (Ye, Miao, Zhao, & Yuan, 2011). This is also consistent with the increased red tones (a*) in the instrumen-…”
Section: Impact On Lipid Degradation and Acrylamide Formationsupporting
confidence: 80%
See 1 more Smart Citation
“…As to the processes, higher TFA were quantified in the DF, but always below 0.05%, corresponding to low amounts from a health point of view. (Ye, Miao, Zhao, & Yuan, 2011). This is also consistent with the increased red tones (a*) in the instrumen-…”
Section: Impact On Lipid Degradation and Acrylamide Formationsupporting
confidence: 80%
“…Deep‐fried potatoes presented the highest amounts ( p < 0.05) (718‐SFO, 606‐SO, 510‐OO, 369‐CO, in μg/kg), followed by MWG (298‐CO, 280‐SFO, 248‐OO, 186‐SO, in μg/kg) and OV [207‐SO, 144‐CO, 95‐SFO, 75‐OO, in μg/kg). The higher amounts in MWG compared to OV can probably be explained by the direct contact with the crisp plate in the former, with probable increased Maillard reactions extension on the darker spots perceived although the influence of microwaves themselves is not excluded (Ye, Miao, Zhao, & Yuan, ). This is also consistent with the increased red tones (a*) in the instrumental color reading ( p < 0.05) [DF (3) > MWG (−2) > OV (−4)] and yellowness (b*) [DF (29) > MWG (26) > OV (24)] while lightness (L*) was similar on all processing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…So far, too little information is available on the effects of microwaves on the acrylamide formation and interactions between food ingredients. Some authors have suggested that more acrylamide may be formed under microwave heating comparing to conventional heating methods [ 15 , 35 , 84 , 85 , 86 , 87 , 88 ]. A possible explanation for this might be that microwaves offer fast temperature increase in the foods owing to their capacity to generate heat energy inside the food, without requiring any medium as vehicle for heat transfer.…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 99%
“…The surface of the microwave-heated food remains moist and the development of the crust, the taste, the color and also the AA formation is limited [ 85 , 86 ]. Although surface browning is a phenomenon typical of roasted and fried foods, and correlates with acrylamide levels, many studies showed, however, that microwave heating, which does not cause more browning of food, can result in more acrylamide formation than conventional heating [ 15 , 35 , 85 , 86 , 87 ]. It can be concluded that, unlike conventional heating, microwave heating can cause acrylamide formation throughout the entire product without its intensive generation in the surface layer.…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 99%
“…In recent studies, some important transient intermediates, such as 3-aminopropionamide (3-APA), methylglyoxal (MG), and HMF, were found to participate the formation of AA in Maillard model systems and in food matrix (Granvogl et al 2004;Granvogl and Schieberle 2006;Yuan et al 2008aYuan et al , 2008bYe et al 2011;Gökmen et al 2012). In the study of Gökmen et al (2012), they found that in the Maillard model systems HMF is a potent carbonyl for accelerating AA formation during heating by the method of in-depth high resolution mass spectrometry and kinetics analysis.…”
Section: Introductionmentioning
confidence: 99%